ANALISIS DAMPAK INTERFERENSI TERHADAP KUALITAS SINYAL JARINGAN LONG RANGE FREKUENSI 920MHZ-923MHZ (AS2) - Hendro FJ Lami; Stephanie I Pella (Jurnal Media Elektro, 2022)
This study modeled the interference between the Lora system signal in the AS2 frequency band and a non-Lora radio signal. Two Lora devices operate on uplink and downlink at a frequency of 923.2MHz to send and receive data on the bandwidth of 125KHz, 250KHz, and 500KHz. The interference generator device is composed of a single board computer installed by the RPITX application. In addition, there is a GNU-Radio application to monitor data and signal transmission levels. Signal quality tests (RSSI, SNR, and time-on-air(ToA)) were carried out under line-of-sight (LOS) conditions and used reference distances of 1m and 4m. The ToA test shows that the greater the bandwidth, the smaller the ToA value, while the change in distance does not affect the ToA. The RSSI test shows that the change in distance affects the RSSI value more significantly than the change in bandwidth. The presence of an interference signal does not significantly affect the RSSI value. SNR testing shows that the greater the bandwidth, the smaller the SNR and significantly decreases when interference occurs.